Effects of blocked versus interleaved presentation on children’s vocabulary learning: a pilot study - Tan Li Ning, N; Bishop, DVM; Parker, AJ (Center for Open Science, 2020)
In some educational contexts, it has been shown that interleaved presentation (i.e. alternating different tasks/skills) results in better learning than blocked presentation (i.e. practising one task/skill at a time). However, this interleaving effect has been studied in a limited range of contexts. Here, we examined whether blocked versus interleaved presentation influenced vocabulary learning in 56 children aged from 6 to 10 years old. We devised a novel online game involving two tasks. The first was a vocabulary learning task, in which children matched spoken words to images of novel animals. The second was a comprehension task, where the children arranged objects to match the spatial relations described in a spoken sentence. Stimuli were presented in a between-subjects design, such that trials from each task either occurred in blocks of 10 or were fully interleaved. Our analysis revealed vocabulary learning in both conditions, but the rate of learning did not differ for participants assigned to the blocked vs interleaved conditions. We did not, however, use posttest assessment means, so we cannot rule out any benefit of interleaving that may emerge after the initial learning phase.